Influence of the Seismic Wave Velocity of the Damage Zone on Near-Field Ground Motions - Wang, Qiankuan; Qiu, Shili; Cheng, Yao; Li, Ping; Kou, Yongyuan; Zhang, Shirui (Frontiers in Earth Science, 2021)
In burst-prone deep underground engineering, seismic waves generated from a near-field ground motion event may play a critical role in causing localized rockburst damage. Accurate estimation of near-field ground motions around excavations is important for seismic hazard risk assessment and dynamic rock support design in underground engineering. During the excavation of an underground cavern, stress redistribution in the surrounding rock leads to the formation of damage zones, including the excavation damage zone (EDZ) and excavation fracture zone (EFZ). The poor properties of the rock in the damage zones cause the wave velocities of the rock mass to decrease and the dynamic wave interaction to change, thereby affecting the ground motions around the excavation. This paper studies the near-field ground motion behavior and reveals the control effect of the seismic wave velocity in the damage zones on the near-field ground motions by the aid of the finite fracturing source model (FFSSM). The research results provide a new knowledge of the influence of excavation disturbance on the ground motion distribution around the excavation, and provide new ideas for the seismic hazard risk assessment and prevention in underground engineering.